PEMANFAATAN PERPUSTAKAAN DIGITAL DI SMA NEGERI 1 MAROS - Aisyah, Nur; Ardiansyah, Muhammad; Habibah, Sitti (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to determine the utilization of the digital library at SMA Negeri 1 Maros. The research focuses on how students use the digital library to support learning activities, increase reading interest, reduce dependence on teachers, and improve efficiency in searching for learning resources. This study employs a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The research informants consist of five students from different grade levels, two teachers, and one librarian. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The results of the study indicate that the utilization of the digital library at SMA Negeri 1 Maros has a positive impact on improving access to learning resources, enhancing students’ reading interest, and fostering independent learning, although there are still challenges related to internet connectivity and some students’ preference for printed books.